1984
DOI: 10.1161/01.cir.69.5.880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and long-term survival of patients with variant angina.

Abstract: We studied 109 consecutive patients with variant angina who underwent cardiac catheterization over an 1 1 year period. All patients were followed for at least 6 months or until death, and 46 patients (22 treated medically and 24 treated surgically) were followed for 5 years or more. Of the 62 patients initially treated medically, 14 had nonfatal myocardial infarctions (12 within 1 month of catheterization) and 12 died (six within 6 months). Survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
35
2
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(48 citation statements)
references
References 26 publications
7
35
2
4
Order By: Relevance
“…Most authors believe that this treatment can reduce the risk of sudden death if it prevents angina attacks [18,22,23]. Our observations are in agreement with this opinion.…”
Section: Discussionsupporting
confidence: 92%
“…Most authors believe that this treatment can reduce the risk of sudden death if it prevents angina attacks [18,22,23]. Our observations are in agreement with this opinion.…”
Section: Discussionsupporting
confidence: 92%
“…A similar pattern has been noted in previous studies. 18,35 Multivariate analysis indicated that only intake of calcium antagonists, extent and severity of coronary artery disease, and ST segment elevation in both the anterior and inferior leads were significant independent predictors of survival without myocardial infarction. The previous studies16-18 indicated that the single most important prognostic factor for survival without myocardial infarction in patients with variant angina was the extent and severity of coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are still some controversies as to the indication and timing of coronary artery bypass surgery for variant angina, 15,18 and there are few reports studying the long-term prognosis for patients with variant angina who underwent coronary artery bypass surgery as compared with those who received only drug treatments. '5 In the present study, we followed 245 consecutive patients with variant angina for periods of 3-15 years (average, 7 years) and examined the factors influencing the long-term prognosis for patients with variant angina, including the use of calcium antagonists and coronary artery bypass surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4] A few aspects of these studies should be noted in considering clinical implications of their results. First, they apparently included a large number of patients who were not treated with calcium blockers.3 '4 It has been suggested that treatment with calcium blockers may reduce the rate of cardiac events in patients with vasospastic angina.3'5 Since these drugs are currently widely used in the treatment of vasospastic angina,6 the long-term prognosis of today's patient with vasospastic angina might be different from that reported in previous studies.`Second, a large portion of the patients in the previous studies had significant atherosclerotic coronary artery disease.`Thus, the results of previous studies may not be applicable to patients with insignificant atherosclerotic disease.…”
mentioning
confidence: 99%